Selective plane illumination optical and optoacoustic microscopy for postembryonic imaging. Issue 5 (8th September 2015) - Lin, Hsiao‐Chun Amy; Chekkoury, Andrei; Omar, Murad; Schmitt‐Manderbach, Tobias; Koberstein‐Schwarz, Benno; Mappes, Timo; López‐Schier, Hernán; Razansky, Daniel; Ntziachristos, Vasilis
<x xml:space="preserve">Abstract</x> Intravital imaging of large specimens is challenging for postembryonic studies. While selective plane illumination microscopy (SPIM) has been widely used to volumetrically visualize organisms, its performance quickly deteriorates for opaque tissues. To overcome this limitation, SPIM was combined with optoacoustic imaging in a hybrid system. A juvenile zebrafish was imaged, revealing high‐resolution results over extended depths of scattering content. This method may enable future visualization of opaque organisms throughout their entire development.